Angle-closure glaucoma, iris-lens contact, ciliochoroidal effusion, and transient myopia induced by topiramate - T. V. Sokolovskaya; V. N. Yashina; N. A. Mahno (Офтальмохирургия, 2021)
Topiramate is a sulphonamide derivative indicated in the treatment of epilepsy and migraine. In foreign scientific literature there are reported cases of topiramate-induced bilateral angle-closure glaucoma and acute myopia with ciliochoroidal effusion.Purpose. To evaluate outcomes of laser iridectomy in a patient with topiramate-induced angle-closure glaucoma and acute myopia with ciliochoroidal effusion.Material and methods. A case is reported of bilateral angle-closure glaucoma, iris-lens contact, ciliochoroidal detachment and acute myopia following topiramate for migraine treatment in a 32-year-old patient. Laser peripheral iridectomy was performed in the both eyes according to the standard technology (Nd:YAG laser Selecta Trio, Lumenis Ltd., Israel) to decrease IOP and restore visual functions.Results. After laser iridectomy, the examination showed normal IOP with no medication, ciliochoroidal effusion and induced myopic shift were relieved.Conclusion. Laser iridectomy is an effective and safe in the treatment of topiramate-induced angle-closure glaucoma, acute myopia, and ciliochoroidal detachment. It contributes to normalization of IOP and improvement of visual acuity.